Local shape volume alterations in subcortical structures of suicide attempters with major depressive disorder. Issue 17 (17th August 2020) - Kang, Wooyoung; Shin, Jeong‐Hyeon; Han, Kyu‐Man; Kim, Aram; Kang, Youbin; Kang, June; Tae, Woo‐Suk; Paik, Jong‐Woo; Lee, Hae‐Woo; Seong, Joon‐Kyung; Ham, Byung‐Joo
Abstract: Suicide is among the most important global health concerns; accordingly, an increasing number of studies have shown the risks for suicide attempt(s) in terms of brain morphometric features and their clinical correlates. However, brain studies addressing suicidal vulnerability have been more focused on demonstrating impairments in cortical structures than in the subcortical structures. Using local shape volumes (LSV) analysis, we investigated subcortical structures with their clinical correlates in depressed patients who attempted suicide. Then we compared them with depressed patients without a suicidal history and age‐ and sex‐matched healthy controls (HCs; i.e., 47 suicide attempters with depression, 47 non‐suicide attempters with depression, and 109 HCs). Significant volumetric differences were found between suicidal and nonsuicidal depressed patients in several vertices: 16 in the left amygdala; 201 in the left hippocampus; 1, 057 in the left putamen; and 140 in the left pallidum; 1 in the right pallidum; and 6 in the bilateral thalamus. These findings indicated subcortical alterations in LSV in components of the limbic–cortical–striatal–pallidal–thalamic circuits. Moreover, our results demonstrated that the basal ganglia was correlated with perceived stress levels, and the thalamus was correlated with suicidal ideation. We suggest that suicidality in major depressive disorder may involve subcortical volume alterations. Abstract : Using local shape volumes (LSV) analysis, significant volumetric differences were found between suicidal and nonsuicidal depressed patients in the left amygdala, left hippocampus, left putamen, bilateral pallidum, and thalamus. These findings propose that suicidality in major depressive disorder may involve subcortical volumetric alterations.